CarMax : incumbent market leader facing new challenge - Jia, Yankun; Winters, David, ctive 2021; Gentry, Richard J. (London : SAGE Publications: SAGE Business Cases Originals, 2021)
CarMax, the leader in the used car dealership market, is facing challenges from both existing competitors and new entrants. CarMax achieved its leader position by improving transparency in the customers' selection and purchasing process, which has led to a better customer experience. However, the used car dealership market is now shaken by the new wave of e-commerce. CarMax needs to adjust its strategy to better compete with its rivals in this new environment. To win the competition, CarMax needs to understand its capabilities and the available choices to formulate a viable strategy. How CarMax can maintain its own advantages and avoid becoming the test-drive center for the emerging online-only used car dealerships are crucial in its strategic change.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; Automobile industry and trade -- Case studies